Edukasi Kesehatan tentang Pengendalian Vektor Sebagai Upaya Meningkatkan Pengetahuan dan Sikap Masyarakat di Desa Nga Lhoksukon Barat - Erna Safitri; Yosinda Yosinda; Susanti Lesiana Sari (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2026)
Vector-borne diseases remain a public health issue in Indonesia. Low levels of community knowledge and poor attitudes regarding vector control can increase the risk of disease transmission. This community service activity aimed to improve community knowledge and attitudes through health education on vector control in West Lhoksukon Nga Village, North Aceh Regency. The activity employed a one-group pretest-posttest design involving 30 participants selected via purposive sampling. Education was delivered through lectures, discussions, and question-and-answer sessions. Evaluation was conducted using questionnaires administered before (pretest) and after (posttest) the educational intervention. Data were analyzed using univariate and bivariate methods, specifically the Paired Sample t-test, with a 95% confidence level (α=0.05). The results showed that the proportion of participants with a good level of knowledge increased from 70.0% to 93.5%, while the proportion with positive attitudes rose from 60.0% to 90.0% following the education. Statistical tests revealed significant improvements in both knowledge levels (p=0.006) and community attitudes (p=0.001). Health education on vector control is effective in enhancing community knowledge and attitudes, thereby serving as a valuable strategy to support the prevention of vector-borne diseases at the community level.